9.5k views
0 votes
Find the solution of the given initial value problem:

(a) y' + 2y = te^{-2t}, y(1) = 0

(b) t^{3}y' + 4t^{2}y = e^{-t}, y(-1) = 0

User Soliz
by
5.8k points

2 Answers

5 votes

Answer:

a.
y(t)=(t^2e^(-2t))/(2)-(1)/(2)e^(-2t)

b.
y=-t^(-3)e^(-t)-t^(-4)e^(-t)

Explanation:

We are given that

a.
y'+2y=te^(-2t),y(1)=0

Compare with
y'+P(t)y=Q(t)

We have P(t)=2,Q(t)=
te^(-2t)

Integration factor=
\int e^(2dt)=e^(2t)


y\cdot I.F=\int Q(t)\cdot I.F dt+C

Substitute the values then, we get


y\cdot e^(2t)=\int te^(-2t)\cdot e^(2t) dt+C


y\cdot e^(2t)=\int tdt+C


ye^(2t)=(t^2)/(2)+C

Substitute the values x=1 and y=0

Then, we get
0\cdot e^2=(1)/(2)+C


C=-(1)/(2)

Substitute the value in the given function


ye^(2t)=(t^2)/(2)-(1)/(2)


y=(t^2)/(2)e^(-2t)-(1)/(2)e^(-2t)

Hence,
y(t)=(t^2e^(-2t))/(2)-(1)/(2)e^(-2t)

b.
t^3y'+4t^2y=e^(-t),y(-1)=0


y'+(4)/(t)y=(e^(-t))/(t^3)


P(t)=(4)/(t),Q(t)=(e^(-t))/(t^3)

I.F=
\int e^{(4)/(t)dt}=e^(4lnt)=e^(lnt^4)=t^4


y\cdot \frac{t^4}=\int e^(-t)(t^4)/(t^3) dt+C


y\cdot t^4=\int te^(-t)dt+C


yt^4=-te^(-t)+\int e^(-t) dt+C


u\cdot v dt=u\int vdt-\int ((du)/(dt)\cdot \int vdt)dt


yt^4=-te^(-t)-e^(-t)+C

Substitute the values x=-1,y=0 then, we get


0=-(-1)e-e+C


C+e-e=0

C=0

Substitute the value of C then we get


yt^4=-te^(-t)-e^(-t)


y=-t^(-3)e^(-t)-t^(-4)e^(-t)

User Nthall
by
6.1k points
4 votes

Answer:


(a)\ y(t) =\ 4.e^(2(1-t))\ +\ (t^2e^(-2t))/(4)


(b)\ y(t)=\ (1-t)e^(-t)\ -\ 2e

Explanation:

(a)
y'\ +\ 2y\ =\ te^(-2t),\ y(1)\ =\ 0


=>\ (D+2)y\ =\ te^(-2t)

To find the complementary function

D+2 = 0

=> D = -2

So, the complementary function can by given by


y_c(t)\ =\ C.e^(-2t)

Now, to find particular integral


(D+2)y_p(t)\ =\ te^(-2t)


=>y_p(t)\ =\ ( te^(-2t))/(D+2)


=\ ( te^(-2t))/(-2+2)

= not defined

So,


y_p(t)\ =\ ( t^2e^(-2t))/(D^2)


=\ (t^2e^(-2t))/((-2)^2)


=\ (t^2e^(-2t))/(4)

So, complete solution can be given by


y(t)\ =\ y_c(t)\ +\ y_p(t)


=> y(t) =\ C.e^(-2t)\ +\ (t^2e^(-2t))/(4)

As given in question


=>\ y(1)\ =\ C.e^(-2)\ +\ (1^2e^(-2))/(4)


=>\ 0\ =\ C.e^(-2)\ +\ (1^2e^(-2))/(4)


=>\ C\ =\ 4e^2

Hence, the complete solution can be give by


=>\ y(t) =\ 4e^2.e^(-2t)\ +\ (t^2e^(-2t))/(4)


=>\ y(t) =\ 4.e^(2(1-t))\ +\ (t^2e^(-2t))/(4)

(b)
t^(3)y'\ +\ 4t^(2)y\ =\ e^(-t),\ y(-1)\ =\ 0


=>\ y'\ +\ 4t^(-1)y\ =\ t^(-3)e^(-t)

Integrating factor can be given by


I.F\ =\ e^{\int (4t^(-1))dt}


=\ e^(log\ t^4)


=\ t^4

Now , the solution of the given differential equation can be given by


y(t)* t^4\ =\ \int t^(-3)e^(-t)t^4dt\ +\ C


=>\ y(t)\ =\ \int t.e^(-t)dt\ +\ C


=\ (1-t)e^(-t)\ +\ C

According to question


y(-1)\ =\ (1-(-1))e^1\ +\ C


=>\ 0\ =\ 2e\ +\ C


=>\ C\ =\ -2e

Now, the complete solution of the given differential equation cab be given by


y(t)\ =\ (1-t)e^(-t)\ -\ 2e

User Apurv Agarwal
by
5.8k points